ASSEMBLY LINE BALANCING PROBLEM WITH HIERARCHICAL WORKER ASSIGNMENT, POSITIONAL CONSTRAINTS, TASK ASSIGNMENT RESTRICTIONS AND PARALLEL WORKSTATIONS - Topaloglu Yildiz, Seyda; Yildiz, Gokalp; Okyay, Raziye (International Journal of Industrial Engineering: Theory, Applications and Practice, 2020)
In this paper, we consider the assembly line balancing problem with hierarchical worker assignment, positional constraints, station paralleling options, and task assignment restrictions. The objective of this problem is to decide on the number of parallel stations to be opened in each work stage and to assign tasks and workers to stations such that the sum of station opening costs and worker costs is minimized. To solve this problem, we initially propose an integer programming model and then develop a simulated annealing algorithm with a local search procedure. A set of test problems are solved using both the proposed IP model, hybrid simulated annealing and original simulated annealing algorithms. The computational results show the effectiveness and efficiency of the proposed hybrid simulated annealing algorithm.